The effect of wall mobility on mass flow in a slow-moving long-stroke stage - A. G. Nikiforov; L. A. Muslova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In modern models and calculation methods of existing high-speed reciprocating compressors, the mobility of the walls is not considered due to the insignificant value and insignificant effect on the efficiency of the working process. Low — speed piston machines currently being developed at Omsk State Technical University have a number of features — first of all, an elongated cylinder, subject to large deformations compared to existing analogues and a long compression time. Which naturally significantly affects the flow of the workflow. The conducted studies have shown that not considering the mobility of the walls can lead to significant errors obtained when modeling the working process of low-speed reciprocating compressors.